Novel solution for luminal access loss into the double-layered LVIS Blue™ construct. Issue 5 (October 2017) - Kouznetsov, Evgueni; Haldis, Thomas; Manchak, Michael; Drofa, Alexander
We described a novel solution for a challenging case of double-layered LVIS Blue™ (LB) stent construct retraction into a large cavernous aneurysm. The double-layered LB stent construct was used as a flow diverter for treatment of a large cavernous aneurysm. Our solution comprised a balloon angioplasty and placement of balloon-mounted cardiac-stent construct through the side wall of the LB construct, with eventual placement of a Pipeline Flex inside of the final conduit.